2001
DOI: 10.1093/jexbot/52.363.2023
|View full text |Cite
|
Sign up to set email alerts
|

Protecting against water loss: analysis of the barrier properties of plant cuticles

Abstract: The cuticle is the major barrier against uncontrolled water loss from leaves, fruits and other primary parts of higher plants. More than 100 mean values for water permeabilities determined with isolated leaf and fruit cuticles from 61 plant species are compiled and discussed in relation to plant organ, natural habitat and morphology. The maximum barrier properties of plant cuticles exceed that of synthetic polymeric films of equal thickness. Cuticular water permeability is not correlated to the thickness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
564
0
11

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 787 publications
(609 citation statements)
references
References 53 publications
20
564
0
11
Order By: Relevance
“…Wax composition controls the cuticular functions, of which blocking excessive water loss is typically considered foremost (Kerstiens, 1996;Riederer and Schreiber, 2001). Studies using the same methods as those employed here showed mean water resistances across species for leaves and fruit of 35 3 10 4 and 1 3 10 4 s m 21 , respectively (Kerstiens, 1996;Schreiber and Riederer, 1996).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Wax composition controls the cuticular functions, of which blocking excessive water loss is typically considered foremost (Kerstiens, 1996;Riederer and Schreiber, 2001). Studies using the same methods as those employed here showed mean water resistances across species for leaves and fruit of 35 3 10 4 and 1 3 10 4 s m 21 , respectively (Kerstiens, 1996;Schreiber and Riederer, 1996).…”
Section: Discussionmentioning
confidence: 68%
“…It has been proposed that wax molecules align in parallel in all-trans conformation to form crystalline domains (Small, 1984), which in turn hinder water penetration by forcing individual molecules to weave a tortuous path around them (Reynhardt, 1997;Riederer and Schreiber, 2001). It should be noted that the chain length profiles of different compound classes within C. bipinnatus petal waxes differed drastically, with relatively short chain lengths (mainly C 22 /C 24 ) for fatty acids and primary alcohols and much longer chain lengths (mainly C 27 /C 29 ) for the co-occurring alkanes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant cuticle is a critical structure for desiccation protection of sporophytes in vascular plants (Riederer and Schreiber, 2001). Here we demonstrate that the cuticle plays a similar role in bryophytes but, unlike in vascular plants, this cuticle is produced by a maternal gametophyte tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Cuticle function relating to water loss has been studied primarily in angiosperms and less so in other tracheophyte lineages (e.g. Riederer and Schreiber, 2001;Schreiber and Schönherr, 2009). Cuticles on the leafy gametophytes of mosses may also function in decreasing water loss (i.e.…”
Section: Introductionmentioning
confidence: 99%